1995
DOI: 10.1101/gad.9.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Cascade regulation of terminal adipocyte differentiation by three members of the C/EBP family of leucine zipper proteins.

Abstract: Terminal differentiation of cultured 3T3-L1 fibroblasts to the adipogenic phenotype is potently stimulated by dexamethasone (DEX) and methylisobutylxanthine (MIX). Previous studies have shown that these hormones induce the expression of genes encoding two members of the CCAAT/enhancer binding protein (C/EBP) family of transcription factors. In the absence of new protein synthesis DEX activates the gene encoding C/EBP~. Likewise, MIX is a direct inducer of C/EBP~ gene expression. Optimal conditions for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
727
3
7

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 845 publications
(766 citation statements)
references
References 57 publications
(59 reference statements)
29
727
3
7
Order By: Relevance
“…Therefore, the entire Mad gene family is not expressed in every di erentiating tissue and may require cell-type speci®c cues. These results also strongly suggest that the transcription of individual Mad genes does not depend on prior expression of other Mad family members, and that their sequential expression is not a true cascade as such has been demonstrated for myogenic transcription activators and the C/EBPs (Weintraub, 1993;Yeh et al, 1995). As the MAD proteins function as transcriptional repressors, the opposite situation, in which cross downregulation occurs might be expected.…”
Section: Sequential Expression Of Mad Family Genessupporting
confidence: 54%
“…Therefore, the entire Mad gene family is not expressed in every di erentiating tissue and may require cell-type speci®c cues. These results also strongly suggest that the transcription of individual Mad genes does not depend on prior expression of other Mad family members, and that their sequential expression is not a true cascade as such has been demonstrated for myogenic transcription activators and the C/EBPs (Weintraub, 1993;Yeh et al, 1995). As the MAD proteins function as transcriptional repressors, the opposite situation, in which cross downregulation occurs might be expected.…”
Section: Sequential Expression Of Mad Family Genessupporting
confidence: 54%
“…Studies in adipogenic cell lines have shown that hormonal induction of differentiation is rapidly followed by expression of C/EBPb, C/EBPd, PPARg and C/EBPa. 5,6 PPARg and C/EBPa induce each other's expression through a positive feedback loop. 7 The latter factors drive the expression of genes that are necessary for lipid synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the C/EBP family are known to have an essential role in adipose tissue development (Cao et al, 1991;Samuelsson et al, 1991;Umek et al, 1991;Freytag and Geddes, 1992;Wang et al, 1995;Yeh et al, 1995) and FUS-CHOP blocks di erentiation of adipogenic precursors in tissue culture (Kuroda et al, 1997;Adelmant et al, 1998). Whereas interference with the normal process of di erentiation may contribute to the oncogenic potential of FUS-CHOP fusion protein, it is a property that they share with the nontransforming germline CHOP gene product (Zinszner et al, 1994;Batchvarova et al, 1995).…”
Section: Introductionmentioning
confidence: 99%